(untitled) (Revista de História Regional, 2007)
Aided by the memories of José Encarnación de Zás, this article will study some hierarchical elements that were used by a civil servant in his relations with local personalities. The aversion between civilized coercion and physical violence emerges from the struggle of these individuals, an opposition that shows us rival groups that competed for power inside the revolutionary Banda Oriental.